Applying a prudential approach in the paradigm of national economic security - Denisevich, Alexander V. (Journal of the Belarusian State University. Law, 2026)
The article reveals the essence of prudential regulation, highlights its main distinctive features, and determines the specifics of applying this approach within the framework of the national security sphere under consideration. The article details the content of ensuring national economic security. It provides a comparative analysis of prudential law and the law of national economic security based on the main goal, subject of regulation, key instruments, and target object of protection, and differentiates the differences between them (epistemological, methodological, functional, and others). It is concluded that the prudential approach provides tactical financial stability, but does not solve the strategic problems of economic security, which require complex political, economic, technological, social, legal, and other measures, because the limitations of its application are associated with the inability to adequately respond to modern non-financial threats. The conducted research has scientific and practical value for the development of the law of national economic security, delineating it from the prudential law in order to eliminate methodological reductionism.
Keywords: prudential regulation; national economic security law; рaradigm gap; methodological reductionism